The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/hel.12456
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan‐ vs proton‐pump inhibitor‐based first‐line 7‐day triple therapy for clarithromycin‐susceptible Helicobacter pylori: A multicenter, prospective, randomized trial

Abstract: The eradication rate of V-AC treatment in the CAM-susceptible H. pylori-infected patients was <90%, as was that by PPI-AC, thus V-AC is not ideal regimen in CAM-susceptible H. pylori. However, the 82.9% eradication rate of V-AC in the CAM-resistant infections may indicate the potential of V-AC with modified dose, dosing interval, and treatment duration. (UMIN000016337).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 31 publications
(54 reference statements)
3
105
2
Order By: Relevance
“…As stated in the 2 RCTs included in our analysis, either vonoprazan‐based or PPI‐based therapy can achieve high eradication rates in patients with clarithromycin‐susceptible strains, while in patients with clarithromycin‐resistant strains both therapies achieved lower eradication rates . These data emphasize the importance of antibiotic resistance to the failure of eradication therapy.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…As stated in the 2 RCTs included in our analysis, either vonoprazan‐based or PPI‐based therapy can achieve high eradication rates in patients with clarithromycin‐susceptible strains, while in patients with clarithromycin‐resistant strains both therapies achieved lower eradication rates . These data emphasize the importance of antibiotic resistance to the failure of eradication therapy.…”
Section: Discussionsupporting
confidence: 64%
“…Dong et al demonstrated that the odds ratio for H. pylori eradication using vonoprazan‐based therapy as compared to conventional PPI‐based therapy was greater for patients infected with clarithromycin‐resistant strains (OR: 5.92) than for patients infected with clarithromycin‐susceptible strains (OR: 2.02). Our results, based on data including that of the most recently published RCT on vonoprazan vs PPI in triple therapy for H. pylori eradication, also suggest that the efficacy of vonoprazan‐based triple therapies may be greatly affected by clarithromycin susceptibility …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The H. pylori status of all participants was determined using a urea breath test (UBT), H. pylori stool antigen test, detection of anti‐ H. pylori IgG, rapid urease test, or H. pylori culture (same procedure as in our previous study) (Table ). Endoscopy was performed within 1 year in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…A large Japanese trial comparing vonoprazan vs PPI in first‐line triple therapy reported a significantly higher eradication rate with vonoprazan (90.8%) compared to esomeprazole (77.5%) or rabeprazole (68.4%) . The eradication rates of vonoprazan with amoxicillin and clarithromycin in clarithromycin‐resistant patients were 82.9% …”
Section: Vonoprazanmentioning
confidence: 99%